Preparing for Portfolio careers in Australian Music: setting a research agenda - Bartlett, Bridie-Leigh; Bennett, Dawn; Bridgstock, Ruth; Draper, Paul; Harrison, Scott; Schippers, Huib (Australian Society for Music Education, 2012)
In the twenty-first century, Australian musicians increasingly maintain 'portfolio' careers, in which they combine diverse employment arrangements and activities. Often, these incorporate industry sectors outside of music. This career pattern is widespread but not well understood, largely because of the limitations of existing research. The lack of knowledge about musicians' work and careers means that Australia currently may not provide appropriate and effective policy, funding, initial training and continuing career support across the diverse music sector. This article discusses existing research relating to the careers and skilling needs of musicians in Australia, and outlines a targeted agenda for further research that has the potential to inform stronger alignment between the requirements of building sustainable music careers and musicians' education and training.